SEM-PLS UNTUK ANALISIS STRUKTUR KEMISKINAN DI PROVINSI JAWA TENGAH TAHUN 2017 - Riyanti, Agustina (Journal of Mathematics and Mathematics Education, 2018)
Abstract:Poverty is a global and national issue that is the government's concern. Poverty alleviation is one of the national priorities in the RKP (Government Work Plan) 2018. The objective of this study is to observe the structure of poverty in Jawa Tengah Province on 2017. In the second semester of 2017, the percentage of poor people in Jawa Tengah Province is 12.23 % which is the second largest percentage on Java Island. The causes of poverty are complex and cannot be measured directly because they contain latent variables. One of the methods of analysis can used for the latent variable is Structural Equation Modeling- Partial Least Square. This method can estimate the relationship between variables that are multiple-relationship and describe the relationship pattern between latent variables and indicator variables with more flexible assumption. The structure of poverty in this study was approached with economic dimension, human resource dimension, and health dimension. The result of this research is obtained 10 valid and reliable indicators from 11 indicators which studied. The result of estimation with bootsrap showed that the dimension of human resources has a significant effect on the economic dimension, the health dimension has a significant effect on human resource dimension, and then the dimension of human resources has significant effect to the economic dimension. In addition, it can be concluded that the economic and health dimensions have a significant effect on the dimension of poverty.Keywords: Poverty, PLS, SEM.